Effects of Genotype and Growth Temperature on the Contents of Tannin, Phytate and In Vitro Iron Availability of Sorghum Grains. - Gangcheng Wu; Stuart K Johnson; Janet F Bornman; Sarita J Bennett; Vijaya Singh; Azra Simic; Zhongxiang Fang (PLoS ONE, 2016)
BACKGROUND:It has been predicted that the global temperature will rise in the future, which means crops including sorghum will likely be grown under higher temperatures, and consequently may affect the nutritional properties. METHODS:The effects of two growth temperatures (OT, day/night 32/21°C; HT 38/21°C) on tannin, phytate, mineral, and in vitro iron availability of raw and cooked grains (as porridge) of six sorghum genotypes were investigated. RESULTS:Tannin content significantly decreased across all sorghum genotypes under high growth temperature (P ≤0.05), while the phytate and mineral contents maintained the same level, increased or decreased significantly, depending on the genotype. The in vitro iron availability in most sorghum genotypes was also significantly reduced under high temperature, except for Ai4, which showed a pronounced increase (P ≤0.05). The cooking process significantly reduced tannin content in all sorghum genotypes (P ≤0.05), while the phytate content and in vitro iron availability were not significantly affected. CONCLUSIONS:This research provides some new information on sorghum grain nutritional properties when grown under predicted future higher temperatures, which could be important for humans where sorghum grains are consumed as staple food.